Indústria cultural em Theodor W. Adorno - Matheus, Daniel Lopes Prado (2024)
This research aims to understand the concepts of modernity and culture industry in Theodor W. Adorno, mainly through the understanding of the author's key work Dialectic of Enlightenment, written in intellectual cooperation with Max Horkheimer. Topics that permeate Theodor W. Adorno's philosophy are researched, namely enlightenment, modern class society, the culture industry and the mass deception of society. The loss of subjectivity is one of the themes studied, as this is one of the striking characteristics of the culture industry. In the same way, the relationships between the culture industry and individuals are analyzed, which becomes that of subject-client or subject-employee. The almost impossible resistance to the culture industry on the part of the subject and to its entire inherent system is an essential part of what Adorno and Horkheimer define as the new ideology